Multifaceted plant responses to circumvent Phe hyperaccumulation by downregulation of flux through the shikimate pathway and by vacuolar Phe sequestration. (8th November 2017) - Lynch, Joseph H.; Orlova, Irina; Zhao, Chengsong; Guo, Longyun; Jaini, Rohit; Maeda, Hiroshi; Akhtar, Tariq; Cruz‐Lebron, Junellie; Rhodes, David; Morgan, John; Pilot, Guillaume; Pichersky, Eran; et al.
Summary: Detrimental effects of hyperaccumulation of the aromatic amino acid phenylalanine (Phe) in animals, known as phenylketonuria, are mitigated by excretion of Phe derivatives; however, how plants endure Phe accumulating conditions in the absence of an excretion system is currently unknown. To achieve Phe hyperaccumulation in a plant system, we simultaneously decreased in petunia flowers expression of all three Phe ammonia lyase (PAL) isoforms that catalyze the non‐oxidative deamination of Phe to trans ‐cinnamic acid, the committed step for the major pathway of Phe metabolism. A total decrease in PAL activity by 81–94% led to an 18‐fold expansion of the internal Phe pool. Phe accumulation had multifaceted intercompartmental effects on aromatic amino acid metabolism. It resulted in a decrease in the overall flux through the shikimate pathway, and a redirection of carbon flux toward the shikimate‐derived aromatic amino acids tyrosine and tryptophan. Accumulation of Phe did not lead to an increase in flux toward phenylacetaldehyde, for which Phe is a direct precursor. Metabolic flux analysis revealed this to be due to the presence of a distinct metabolically inactive pool of Phe, likely localized in the vacuole. We have identified a vacuolar cationic amino acid transporter ( PhCAT2 ) that contributes to sequestering excess of Phe in the vacuole. In vitro assays confirmed PhCAT2 can transport Phe, and decreased PhCAT2 expression in PAL ‐RNAi transgenic plants resulted in 1.6‐fold increase in phenylacetaldehyde emission. These results demonstrate mechanisms by which plants maintain intercompartmental aromatic amino acid homeostasis, and provide critical insight for future phenylpropanoid metabolic engineering strategies.